Optimasi Penggunaan Energi Pada Sistem Pencahayaan Gedung Bandara Kualanamu Deli Serdang Dalam Rangka Konservasi Energi Menggunakan Metode Algoritma Genetika - Benri Purba; Parlin Siagian; Rahmaniar (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Energy saving must be carried out by the government, companies or the community. The high consumption of electricity is a strong reason to optimise electrical energy and lighting systems in buildings and other public places. In this study, the author uses a genetic algorithm to optimise the use of electrical energy and lighting in the Kualanamu Airport building. Genetic algorithm is a computing technique based on the principle of evolution in genetics. This study aims to test the effectiveness of using genetic algorithms to optimise the lighting system of the Kualanamu Airport building. The data used in this study is real-time data from the MCB power system or the airport building meter. Based on the calculations and analysis carried out in this study, it can be concluded that the AG evaluation presentation test has the best results with an average crossover of 0.3-1, an average mutation of 0.05-0.5 and an average generation of 92, with a fitness value of 1,438.72.